Three-operator splitting scheme with the reference image regularization for electrical capacitance tomography - Lei, J.; Liu, Q. B.; Wang, X. Y. (Neural computing & applications, 2019)
The image reconstruction is an important step in the electrical capacitance tomography (ECT) technology, and its performance directly impacts the reconstruction precision (RP). Beyond existing optimization-based imaging techniques, in this study the data-dependent reference image abstracted by the regularized random vector functional link network (RVFLN) and the domain expertise about imaging targets (ITs) are simultaneously encapsulated as regularizers to form a more effective imaging model. The three-operator splitting (TOS) technique is developed to solve the proposed imaging model more effectively, which extends the flexibility of the TOS method with the improvement in the utilization of image priors. Numerical validation results indicate that the proposed imaging technique achieves better reconstructions as compared with the state-of-the-art methods.